2021
DOI: 10.3389/fendo.2021.599316
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Evolution of Bone Microarchitecture and Bone Strength in Type 2 Diabetic Postmenopausal Women With and Without History of Fragility Fractures—A 5-Year Follow-Up Study Using High Resolution Peripheral Quantitative Computed Tomography

Abstract: IntroductionDiabetic bone disease is characterized by an increased fracture risk which may be partly attributed to deficits in cortical bone quality such as higher cortical porosity. However, the temporal evolution of bone microarchitecture, strength, and particularly of cortical porosity in diabetic bone disease is still unknown. Here, we aimed to prospectively characterize the 5-year changes in bone microarchitecture, strength, and cortical porosity in type 2 diabetic (T2D) postmenopausal women with (DMFx) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 69 publications
1
9
0
Order By: Relevance
“…This may explain the large degree of variation we found between studies and suggests that cortical porosity may reflect presence of multiple diabetes-related complications, although heterogeneity may also reflect variable endosteal contour placement among study centres [ 49 ] that may cause misinterpretation of trabeculae in the endosteal transition zone as porous cortical bone [ 17 ]. Our findings are consistent with a recent longitudinal first-generation HR-pQCT investigation indicating that fracture patients with T2DM had favourable trabecular microarchitecture accompanied by a non-linear rise in cortical porosity [ 50 •]. Enhanced trabecular features possibly reflect a natural compensatory response to T2DM-associated cortical weakness.…”
Section: Discussionsupporting
confidence: 91%
“…This may explain the large degree of variation we found between studies and suggests that cortical porosity may reflect presence of multiple diabetes-related complications, although heterogeneity may also reflect variable endosteal contour placement among study centres [ 49 ] that may cause misinterpretation of trabeculae in the endosteal transition zone as porous cortical bone [ 17 ]. Our findings are consistent with a recent longitudinal first-generation HR-pQCT investigation indicating that fracture patients with T2DM had favourable trabecular microarchitecture accompanied by a non-linear rise in cortical porosity [ 50 •]. Enhanced trabecular features possibly reflect a natural compensatory response to T2DM-associated cortical weakness.…”
Section: Discussionsupporting
confidence: 91%
“…The optimal AGEs cut-off value leading to a high fracture risk was 4.156mmol/L, which suggests postmenopausal T2D patients have an increased fracture risk when the AGEs level is higher than 4.156mmol/L. Previous studies indicated that the impaired bone microarchitecture has a considerable influence on bone strength and is essential in fracture initiation and propagation (50,51). A meta-analysis reported the increase of cortical porosity is relevant to bone quality decline and increased fracture risk.…”
Section: Discussionmentioning
confidence: 97%
“…The HR-pQCT is often referred to as an 'in-vivo bone biopsy' due to its high-resolution capabilities. Most studies involving metabolic health and HR-pQCT-derived bone outcomes focus specifically on diabetes, rather than insulin resistance per se [69][70][71][72]. Nonetheless, these studies provide a potential explanation for the higher fracture risk experienced by individuals with T2D despite greater BMD outcomes as measured via DXA.…”
Section: Bone Health Assessmentmentioning
confidence: 99%